2013
DOI: 10.1111/epi.12063
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulation of gephyrin and GABAA receptor subunits during epileptogenesis in the CA1 region of hippocampus

Abstract: Purpose Epileptogenesis is the process by which a brain becomes hyperexcitable and capable of generating recurrent spontaneous seizures. In humans, it has been hypothesized that following a brain insult there are a number of molecular and cellular changes that underlie the development of spontaneous seizures. Studies in animal models have shown that an injured brain may develop epileptiform activity before appearance of epileptic seizures and that the pathophysiology accompanying spontaneous seizures is associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 53 publications
0
45
1
2
Order By: Relevance
“…These truncated forms of gephyrin contribute to the disassembly of the postsynaptic gephyrin clusters, with a consequent loss of the neuroprotective activity mediated by synaptic GABA A R. Therefore, inhibition of gephyrin cleavage might be a therapeutic target to preserve synaptic inhibition in brain ischemia. Given the recent evidence showing a downregulation of gephyrin during epileptogenesis in the CA1 region of the hippocampus [52], which is associated with the accumulation of gephyrin protein fragments [53,54], strategies aiming at preventing calpainmediated gephyrin cleavage may also be effective in epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…These truncated forms of gephyrin contribute to the disassembly of the postsynaptic gephyrin clusters, with a consequent loss of the neuroprotective activity mediated by synaptic GABA A R. Therefore, inhibition of gephyrin cleavage might be a therapeutic target to preserve synaptic inhibition in brain ischemia. Given the recent evidence showing a downregulation of gephyrin during epileptogenesis in the CA1 region of the hippocampus [52], which is associated with the accumulation of gephyrin protein fragments [53,54], strategies aiming at preventing calpainmediated gephyrin cleavage may also be effective in epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the upregulation of GABA A Rs and gephyrin proteins contributes to iLTP expression, while their downregulation has been observed during status epilepticus in the CA1 region of the hippocampus (Peng et al, 2004; González et al, 2013; Petrini et al, 2014). Moreover, it has been reported that fear conditioning regulates the gene expression of gephyrin in the amygdala (Ressler et al, 2002; Chhatwal et al, 2005).…”
Section: Additional Mechanisms For the Postsynaptic Control Of Inhibimentioning
confidence: 99%
“…AEİ'ler ile enflama- [76] Altta yatan mekanizma transkripsiyonel faktörlere bağlı görünmekle birlikte metabolik fonksiyonların yetersizliği de dikkat çeki-cidir. Mitokondriyal fonksiyonun yetersizliği ve ATP kullanı-labilirliğinin azalması reaktif oksijen substratlarını (ROS) artırdığından, hedef moleküllerde hızlı değişikliklerle birlikte enerji tüketimi ve ROS aracılı hasar ile uzun dönemde de bu metabolik fonksiyon yetersizliğinin etkileri gözlenmektedir.…”
Section: Nöromodülatör Sistemlerle Aei̇'lerin Diğer Olası Etkileşmeleriunclassified
“…Bu değişikliklere α4, β2/3 ve γ2 alt ünitelerinin kaybı ve hücre yüzeyindeki reseptörlerin durumunda bir azalmanın eşlik ettiği gösterilmiştir. [76] GABAerjik nörotransmisyondaki eksiklik, GABA-A reseptörleri, reseptör hareketini ve reseptörün membrana yapışarak fonksiyon görmesini sağlayan yapı taşı proteinlerindeki (gefrin, GABARAP [GABA reseptör aracılı protein], GRIP [proteinle etkileşen glutamat reseptör] ve NSF [N-etilmaleimide duyarlı faktör]) ekspresyonel sikliklerinde Alzheimer hastalığı, Parkinson hastalığı veya enflamatuvar bağırsak hastalıklarına yatkınlık oluşur. Uzun süreli farmakolojik inhibisyonu bazı risklerle ilişkili olabilir.…”
Section: Epilepside İlaç Direnciyle İlişkili Diğer öNemli Konular Staunclassified